Under the same sky : from starvation in North Korea to salvation in America - Kim, Joseph, 1990-; Talty, Stephen (Boston : Houghton Mifflin Harcourt, 2015)
'A searing story of starvation and survival in North Korea, followed by a dramatic escape, rescue by activists and Christian missionaries, and success in the United States thanks to newfound faith and courage'--
Keywords: Kim, Joseph, -- 1990-; Refugees -- Korea (North) -- Biography; Immigrants -- United States -- Biography; Victims of famine -- Korea (North).; Human rights -- Korea (North).; Rescue work -- China; Christian ethics -- China; Korea (North) -- 20th century -- Biography